2020
DOI: 10.3390/ijms21051640
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Thr/Tyr kinase Increases the Cancer Progression by Neurotensin and Dihydropyrimidinase-Like 3 in Lung Cancer

Abstract: Lung cancer is one of the leading causes of cancer-related death globally, thus elucidation of its molecular pathology is highly highlighted. Aberrant alterations of the spindle assembly checkpoint (SAC) are implicated in the development of cancer due to abnormal cell division. TTK (Thr/Tyr kinase), a dual serine/threonine kinase, is considered to act as a cancer promoter by controlling SAC. However, the mechanistic details of how TTK-mediated signaling network supports cancer development is still a mystery. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Suppression of MPS1 significantly increased the expression of claudin-1 but decreased the expression of slug and vimentin in KKU-055 and KKU-213A cells. This result is consistent with previous studies showing that vimentin expression was decreased in stable knockdowns of MPS1 in triple negative breast cancer [ 17 ] and lung cancer [ 35 ]. Nevertheless, this current research is the first to demonstrate an increase in claudin-1 and decrease in slug expression after MPS1 knockdown in CCA cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Suppression of MPS1 significantly increased the expression of claudin-1 but decreased the expression of slug and vimentin in KKU-055 and KKU-213A cells. This result is consistent with previous studies showing that vimentin expression was decreased in stable knockdowns of MPS1 in triple negative breast cancer [ 17 ] and lung cancer [ 35 ]. Nevertheless, this current research is the first to demonstrate an increase in claudin-1 and decrease in slug expression after MPS1 knockdown in CCA cells.…”
Section: Discussionsupporting
confidence: 93%
“…Knockdown of MPS1 significantly suppressed cell migration and invasion in KKU-055 and KKU-213A cell lines. These findings are similar to observations reported in bladder [ 14 ], breast [ 17 ], liver [ 15 , 31 ], and lung [ 16 , 35 ] cancers. Epithelial-mesenchymal transition (EMT) is a process involved in the migration and invasion of cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…This synthetic compound acts as an adenosine triphosphate (ATP) analogue which inhibits kinase enzyme activity ( Hiruma et al, 2016 ). Monopolar spindle protein 1 (MPS1) kinase has been reported to promote progression of cancers and MPS1 overexpression was related with poor survival of cancer patients including breast, liver, lung cancers ( Choi et al, 2017 ; King et al, 2018 ; Tsai et al, 2020 ; Xu et al, 2016 ). Laboratory studies revealed that reversine has been shown to inhibit the growth of multiple cancers including colon ( Park et al, 2019 ), prostate ( Hsieh et al, 2007 ), oral squamous ( Lee et al, 2012 ) and thyroid ( Lu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This synthetic compound acts as an adenosine triphosphate (ATP) analogue which inhibits kinase enzyme activity (Hiruma et al 2016). Monopolar spindle protein 1 (MPS1) kinase has been reported to promote progression of cancers and MPS1 overexpression was related with poor survival of cancer patients including breast, liver, lung cancers (Choi et al 2017; King et al 2018;Tsai et al 2020;Xu et al 2016). Laboratory studies revealed that reversine has been shown to inhibit the growth of multiple cancers including colon (Park et al 2019), prostate (Hsieh et al 2007), oral squamous (Lee et al 2012a) and thyroid (Lu et al 2012).…”
Section: Introductionmentioning
confidence: 99%